Metal mobility in an anaerobic-digestate-amended soil: the role of two bioenergy crop plants and their metal phytoremediation potential - Bonet-Garcia, Neus; Baldasso, Veronica; Robin, Valentin; Gomes, Carlos R.; Guibaud, Gilles; Alves, Maria João; Castro, Ricardo; Mucha, Ana Paula; Almeida, C. Marisa R. (Frontiers in Environmental Science, 2023)
Panicum virgatum and Pennisetum alopecuroides, two non-food bioenergy crops were evaluated for their capacity to phyto-manage trace metals (Pb, Zn, Ni, Fe, Mn, Co, Cr, and Cu) from municipal 2 This is a provisional file, not the final typeset article solid waste digestate after its application to a marginal soil. For that, 90-day vertical soil column mesocosm (columns with 0.6 x 0.2 m) experiments were carried out to assess (i) the impact of digestate application on a marginal soil's health, (ii) plant effect on digestate-borne trace metals' mobility along the soil profile (measuring total metal levels and fractionation in different soil layers by atomic absorption spectroscopy, and (iii) plant growth performance and trace metals (Pb, Zn, Cu) uptake capacity. Results showed that trace metals were mostly confined in the 0-0.2 m soil horizon over the course of the experimental period, migrating from the digestate amended soil layer (0-0.1 m) to the layer underneath (0.1-0.2 m) within the first 21 days and remaining stable afterwards. No evidence of trace metals' mobility to deeper soil layers was detected. Trace metals' migration was reduced when P. virgatum and P. alopecuroides were present, suggesting a phytoremediation (phytostabilization) effect. For both plant species, no trace metals accumulation in roots was observed (bioconcentration factor <1) although both plants showed potential for Zn translocation to aboveground tissues (translocation factor >1). The growth of both plants was positively affected by municipal solid waste digestate amendment, which also improved soil quality (increased concentration of total organic carbon and available phosphorus, as well as cation exchange capacity and water holding capacity).